Cytokines profiles in patients with rheumatoid arthritis: Genetic polymorphisms, protein and gene expressions of tumour necrosis factor-x interleukin-18 and interleukin-18 binding proteins - SUPPIAH PARAMALINGAM SIVALINGAM (2010)
Ph.D